A SURVEY STUDY OF PERSONAL LEARNING ENVIRONMENT TOOLS FOR ENGLISH LANGUAGE LEARNING OF THAI EFL UNDERGRADUATE STUDENTS - Ruengkul, Apapan; Sukavatee, Pornpimol (PEOPLE: International Journal of Social Sciences, 2015)
This paper aimed to explore Personal Learning Environment tools for English language learning of Thai EFL undergraduate students. The study used the questionnaire as an instrument to gather the information from the first year public university students studying in foundation English course. These were administered to 150 learners. The data received from the questionnaires were analyzed using the descriptive analysis in percentage. The results indicated that Google and YouTube were mainly used to learn and improve all skills of English, while Facebook was used to focus on learning and improving reading and writing skills. These tools conformed to the key characteristics of Personal Learning Environment (PLE) which were learner control, lifelong learning and various tools. Most students used Google to learn and improve every skill of English since it has been considered as a valuable resource for support independent language learning. It contributed learners to search for the information they desired through the use of keywords. Like Google, YouTube was used to learn and improve all skills of English because it provided a rich resource for learners to explore together with discover educational content. Besides, it offered fast and fun access to language, culture-based videos as well as instruction from all over the globe. For Facebook, it assisted learners to learn and improve their reading and writing skills as well as their collaborative learning. They could share, collaborate or work as a team and critique on each other’s work with easy access.